Inactivation of Listeria monocytogenes and Salmonella Enteritidis in dry-cured ham by combined treatments of high pressure and the lactoperoxidase system or lactoferrin. (October 2015) - de Alba, María; Bravo, Daniel; Medina, Margarita
Abstract: The effect of high hydrostatic pressure (HHP) at 450 MPa for 10 min combined with the lactoperoxidase (LP) system or lactoferrin (LF) on the survival of Listeria monocytogenes and Salmonella Enteritidis in sliced dry-cured-ham during 60 d at 8 °C was investigated. Levels of L . monocytogenes and S . Enteritidis decreased by HHP, whereas were not affected by the LP system or LF applied individually. A synergistic antimicrobial activity was detected on S . Enteritidis at 450 MPa with the LP system or LF. Differences in texture parameters were low and diminished at the end of storage. Lightness ( L *) increased with combined treatments, although differences were attenuated at the end of storage. Redness ( a *) values tended to decrease by HHP applied alone or in combination with antimicrobials. Industrial relevance: Microbial inactivation by high pressure in combination with the lactoperoxidase system or lactoferrin against L. monocytogenes and S. Enteritidis in sliced dry-cured ham during refrigerated storage was improved. Color and texture were slightly changed by treatments. Highlights: HHP and LPS or LF on Salmonella Enteritidis in dry-cured ham was synergistic. HHP + LPS inactivation was 2.1 units higher than the sum of the individual reductions. HHP + LF inactivation was 1.5 units higher than the sum of the individual reductions. Hardness tended to increase slightly without following a specific pattern. L* tended to increase and a* to decrease slightly in treated samples.